Psikoedukasi Soft Skill untuk Meningkatkan Pengetahuan tentang Keterampilan Mengelola Waktu dan Mengelola Stres pada Mahasiswa - Muthia Aryuni (Universitas Tadulako, 2022)
Various problems experienced by students have an impact on the learning process until the completion of student studies. If this problem is allowed to continue, it will have a bad impact on students and faculty. Students may be late in completing their studies until drop out which ultimately affects the accreditation of the faculty of medicine. The problems experienced by students are mostly caused by their lack of skills or ability to solve problems independently. The transition from the previous education level to higher education causes various problems that affect the quality of student academic performance on campus, resulting in behaviors such as procrastination habits to complete assignments, low motivation to learn, poor self-regulation, difficulty managing time, not knowing the appropriate learning method with their personality, and stress. This study aims to increase knowledge about time management and stress management skills in medical faculty students. This research method used a quasi-experimental approach with a quantitative approach. The experimental design used was one-group pretest-posttest. The instrument used was the knowledge test about stress management skills and the knowledge test about time management skills. The results showed that there was an increase in students' knowledge about time management skills in the high category and an increase in stress management skills in the high category.